Effect Of Corporate Size on Corporate Sustainability Disclosure Of Healthcare Companies In Nigeria - Yagana Alhaji Baba (Yayasan Edukasi Cakrawala Nusantara, 2026)
The importance of sustainability reporting disclosure in investment decision process cannot be overemphasized. Corporate size has been originally viewed as affecting component in the investigation of degree of sustainability disclosure but this assertion is yet to be revalidated. On this premise, this study assessed the effect of corporate size on corporate sustainability disclosure of healthcare companies in Nigeria. The research adopted are combination of both qualitative and quantitative design. Data was collected from secondary source and hypothesis tested using regression analysis. Descriptive statistics result showed a moderate level of sustainability disclosure among health companies. The correlation output revealed a positive correlation between corporate size and CSD in healthcare sector of Nigeria. Furthermore, regression result showed that relationship between corporate size and CSD is statistically significant with p-value off 0.000 less than significance value of 0.05. the study concludes that larger companies are likely to disclose more on sustainability report. Therefore, it recommends smaller companies be encouraged to engage in sustainability reporting practice because of relevance it hold in the investment decision making process recently.